AKSIOLOGI TARI BEDHAYA KRATON YOGYAKARTA - Sunaryadi, Sunaryadi (Sekolah Pascasarjana UGM, 2013)
Bedhaya at Palace dance was originally a sacred dance that is laden with symbols of life because itâsnot just a dance movement, but an action that is displayed and that becomes the life reference. Bedhayais presented as a mirror of Javanese culture axiological which includes ethical and aesthetic values . Itis a reflection of manunggaling kawula-Gusti in terms of its ethical dimension and it has the aestheticvalues of the motion, fashion, and makeup. Bedhaya dance philosophy is summaried in the doctrineof ngelmu sangkan paran covering three things: the first itâs related to the human consciousness thatcomes from God (urip iki saka sapa); the second, it is irelated to the duties and obligations of humanbeings in the world (urip iki arep apa); and the third, it is related to manâs return to his Lord (urip ikipungkasane piye). Therefore, in the moral ethics context, Javanese life purpose is how to be a good manto reach the manunggaling kawula with Gusti as it is believed that goodness and beauty (mind) are themanifestation of the Essence of the Most Holy. The journey of human life portrayed in lampah bedhayaof majeng beksa , beksa to mundur beksa is a role model to determine the choice between good and bad .